The use of Sensor Networks to create smart environments - Glória, André Filipe Xavier da (2017)
Internet of Things is taking the world in order to be the next big thing since the Internet, with almost every object being connected to gather data and allow control through mobile and web devices. But this revolution has some barriers with the lack of standardization in communications or sensors. In this dissertation we present a proposal of a system dedicated to creating smart environments using sensor networks, with a practical application developed to achieve automation, efficiency and versatility, allowing real-time monitoring and remote control of any object or environment improving user experience, tasks efficiency and leading to costs reduction. The developed system, that includes software and hardware, is based on adaptive and Artificial Intelligence algorithms and low cost IoT devices, taking advantage of the best communication protocols, allowing the developed system to be suited and easily adapted to any specification by any person. We evaluate the best communication and devices for the desired implementa tion and demonstrate how to create all the network nodes, including the build of a custom IoT Gateway and Sensor Node. We also demonstrate the efficiency of the developed system in real case scenarios. The main contributions of our study are the design and implementation of a novel architecture for adaptive IoT projects focus on environment efficiency, with practical demonstration, as well as comparison study for the best suited communication protocols for low cost IoT devices.